2004
DOI: 10.1007/s00330-003-2143-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the Perclose suture-mediated closure device following carotid artery stenting under clopidogrel platelet blockade

Abstract: The aim of this study was evaluation of a closure device (Perclose, Menlo Park, Calif.) for closure of the femoral artery access site in patients undergoing aggressive anticoagulation and platelet blockade after carotid stenting. Fifty-five patients who received clopidogrel in addition to aspirin and heparin as medication for carotid stenting were included for suture of the femoral access site after using 7- or 8-F guide catheters. The technical success, the time for suture, the clotting parameters, and compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The CREATE Pivotal Trial investigators [42] reported a groin “injury” rate with heparin of 3.3% ( n = 419), with no major clinical sequelae. Zorger and coworkers [43] observed 4% incidence of large hematomas in 54 patients undergoing CS with heparin. A lower 0.6% ( n = 475) groin complication rate was reported using the Perclose device following CS, but this may have been partly due to inconsistent use of heparin [44].…”
Section: Discussionmentioning
confidence: 99%
“…The CREATE Pivotal Trial investigators [42] reported a groin “injury” rate with heparin of 3.3% ( n = 419), with no major clinical sequelae. Zorger and coworkers [43] observed 4% incidence of large hematomas in 54 patients undergoing CS with heparin. A lower 0.6% ( n = 475) groin complication rate was reported using the Perclose device following CS, but this may have been partly due to inconsistent use of heparin [44].…”
Section: Discussionmentioning
confidence: 99%
“…53,196,198,247,[252][253][254][255][256][257][258] Among the general risks is access-site injury, which complicates 5% of cases, but most such injuries involve pain and hematoma formation and are self-limited. [259][260][261][262] Contrast-induced nephropathy has been reported in <1% of cases, because CAS is generally avoided in patients with severe renal dysfunction. 263 The results of observational studies suggest that EPDs reduce rates of adverse events during CAS [264][265][266] when operators are experienced with the apparatus 56 ; in unfamiliar hands, the devices are associated with worse clinical outcomes 67,178,180 and a higher rate of stroke.…”
Section: Carotid Artery Stentingmentioning
confidence: 99%
“…Among the general risks is access-site injury, which complicates 5% of cases, but most such injuries involve pain and hematoma formation and are self-limited (259)(260)(261)(262). Contrast-induced nephropathy has been reported in <1% of cases, because CAS is generally avoided in patients with severe renal dysfunction (263).…”
Section: Carotid Artery Stentingmentioning
confidence: 99%